Tensions between policy aspirations and enactment: assessment and inclusion for refugee background students. Issue 6 (2nd November 2021) - Baak, Melanie; Miller, Emily; Sullivan, Anna; Heugh, Kathleen
ABSTRACT: This article considers the ways in which two senior secondary assessment policies that aim to be inclusive are enacted for students from refugee backgrounds. The final years of secondary school in Australia are shaped by high-stakes assessment requirements. Yet there have been policy moves in South Australia to be more inclusive of students by providing more flexibility for them to demonstrate their learning in diverse ways. We undertook a critical policy analysis to investigate the ways in which South Australian senior secondary certificate policies are enacted in two case study secondary schools. Our analysis of the data indicates that school staff navigate between competing demands of conflicting policy directives. These conflicting directives result in tensions for staff as they enact policies . In high-stakes assessment environments where staff and students strive towards academic achievements, inclusive policies can be limited by other policies that impose uniformity and fairness. The limitations to inclusion noted in this study may be indicative of broader exclusions created by the enactment of policies in high-stakes assessment contexts.